The impacts of complexation and glycated conjugation on the performance of soy protein isolate-gum Arabic composites at the o/w interface for emulsion-based delivery systems. (February 2023) - Feng, Sirui; Guo, Yunsi; Liu, Feng; Li, Zhangpeng; Chen, Kexian; Handa, Akihiro; Zhang, Yue
Abstract: Complexation and glycation conjugation are the two most common routes to prepare protein-polysaccharide based encapsulant materials for food and pharmaceutical applications. It is very necessary to investigate the impacts of the two preparation routes on the structures, physicochemical and functional properties of protein-polysaccharide composites at both molecular and macroscopic levels. In this study, soy protein isolate (SPI)-gum Arabic (GA) composites were prepared through complexation and glycated conjugation and characterized by various analytical techniques. The functionality of SPI/GA composites as encapsulants was evaluated by using eugenol emulsion as a model. The composites prepared by conjugation showed better emulsifying and stabilizing abilities, lower release rate but higher skin penetration ability than complexes, which could be attributed to the slightly better interfacial tension reduction ability and electronegativity. The complexation and conjugation abilities of GA with glycinin (11S) and β-conglycinin (7S), two major individual proteins in SPI, were also evaluated by intrinsic fluorescence quenching method, grafting degree determination and molecular docking. The results indicated that 7S showed higher tendency to form conjugates with GA than 11 S while the two proteins had similar complexation affinities. Findings from this work are promising for the development of SPI-polysaccharide based encapsulation system for food and pharmaceutical applications. Graphical abstract: Image 1 Highlights: SPI-GA composites were prepared by complexation and wet Maillard reaction based-conjugation. Conjugation could better improve the encapsulation efficiency and storage stability of SPI-GA. The better functionality of conjugates was contributed to the interfacial tension reduction ability and electronegativity. The complexation and conjugation abilities of 11S and 7S with GA were firstly evaluated. GA showed higher tendency to form conjugates with 7S rather than 11S.